KATA SERAPAN DALAM BAHASA INDONESIA - ROSTINA . (LP2MTBM MAKARIOZ, 2023)
Indonesian language in its growth and development is always open to the vocabulary of other languages, if in accordance with the rules of absorption of Indonesian words, can be accepted as Indonesian vocabulary either as an absorption vocabulary with adjustments to the rules or as an absorption vocabulary without experiencing spelling adjustments. In the development of the Indonesian language, it also adapts to the changing times. In this context, various elements of absorption enter the Indonesian language, enriching its vocabulary. However, there are various techniques of absorption of foreign elements into Indonesian, through adoption, adaptation, translation and creation techniques. Indonesian has absorbed from various languages, both from regional languages and foreign languages, this absorption word has been recorded since long ago. For example, in the oldest Malay-language inscription (7th century) written in Pallawa letters, there is an absorbed vocabulary from Sanskrit.It can be concluded that absorbed words are one of the fuels for the development of the Indonesian language. The proof is that until now we still rely on these words to speak.